Determinants of infant nutritional status in Dabat district, North Gondar, Ethiopia: A case control study - Wubante, Amarech Asratie (PLoS One, 2017)
BACKGROUND: Malnutrition is the top cause of global burden of disease, disability and mortality among infants. Over two-thirds of deaths of children globally occur during the first year of life (infancy). Malnutrition among infants is substantially high in Ethiopia. Therefore, this study is aimed to assess determinants of infant nutritional status. METHODS: A community based nested case-control study was conducted from February to June 2013 in Dabat district. A total of 80 cases and 320 controls (1:4 ratios) were studied. Relevant data was extracted from the community based survey data set. Anthroplus software was used to identify cases and controls. Determinants of infant nutritional status were identified using multivariate analysis. RESULTS: Among the total of 80 cases and 320 controls, more than half (52.5%) of the cases and the controls (53.8%) were males and females, respectively. Breast Feeding (BF) was started immediately after birth in only 43.8% of the cases. Nearly 94% of the mothers of the cases had no breast feeding information as part of Ante Natal Care (ANC) follow up. Maternal age (AOR: 0.29; 95% CI: 0.11–0.76), having radio (AOR: 0.43; 95% CI: 0.22–0.82), lack of toilet facility (AOR: 2.24; 95% CI: 1.16–4.33), deprivation of colostrum (AOR: 1.76; 95% CI: 1.01–1.06) and method of complementary feeding (AOR: 2.82; 95% CI: 1.33–5.99) were associated with wasting. CONCLUSIONS: This study has found that inappropriate infant feeding; nutritional information gap and lack of toilet facility as significant predictors of malnutrition. Hence, joint interventions, including counseling of mothers about benefits of colostrum feeding and use of appropriate feeding method, toilet utilization and mass media such as radio possession, are needed to address the problem in Dabat district.